2010
DOI: 10.1002/fld.2452
|View full text |Cite
|
Sign up to set email alerts
|

A numerical scheme for Euler–Lagrange simulation of bubbly flows in complex systems

Abstract: SUMMARYAn Eulerian-Lagrangian approach is developed for the simulation of turbulent bubbly flows in complex systems. The liquid phase is treated as a continuum and the Navier-Stokes equations are solved in an unstructured grid, finite volume framework for turbulent flows. The dynamics of the disperse phase is modeled in a Lagrangian frame and includes models for the motion of each individual bubble, bubble size variations due to the local pressure changes, and interactions among the bubbles and with boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…In the Euler-Lagrange approach, the fluid phase is treated as a continuum by solving the Navier-Stokes equations, and the air phase is solved by tracking a large number of particles. In spite of Shams et al (2011), Sungkorn et al (2012 and Dapelo et al (2015) used the Euler-Lagrange approach to simulate the gas behaviors in liquid. This model is not widely applied since the bubble is assumed a rigid sphere.…”
Section: Governing Ow Equationsmentioning
confidence: 99%
“…In the Euler-Lagrange approach, the fluid phase is treated as a continuum by solving the Navier-Stokes equations, and the air phase is solved by tracking a large number of particles. In spite of Shams et al (2011), Sungkorn et al (2012 and Dapelo et al (2015) used the Euler-Lagrange approach to simulate the gas behaviors in liquid. This model is not widely applied since the bubble is assumed a rigid sphere.…”
Section: Governing Ow Equationsmentioning
confidence: 99%
“…Even though not directly applicable to the present study, several models have also been developed and applied to the study of non-spherical bubble dynamics (Chahine, 1982, Zhang et al, 1993, Hsiao & Chahine, 2001, Choi et al, 2009, Wang & Blake, 2010. The Rayleigh-Plesset equation (Rayleigh-Plesset equation) and its small compressibility equivalent models (Herring, 1941, Gilmore, 1952, Keller & Kolodner, 1956), remain however, by far the most widely used models for a wide range of applications involving bubble dynamics such as hydrodynamic cavitating flows (Plesset, 1949, Ceccio & Brennen, 1991, Brennen, 1995, Chahine, 2009, Brennen, 2011, acoustic cavitation applications (Keller & Miksis, 1980, Hilgenfeldt et al, 1998, Moholkar et al, 1999, Prosperetti & Hao, 1999, Calvisi et al, 2007, two-phase bubbly flows (Seo et al, 2010, Shams et al, 2011, Hsiao et al, 2013b, and underwater explosion bubbles (Herring, 1941, Keller & Kolodner, 1956, Chahine & Harris, 1997, Wardlaw & Mair, 1998, Geers & Hunter, 2002, Krieger & Chahine, 2005, de Graaf et al, 2012. This is predominantly because of the success of these methods at recovering the key physics involved in each application and because of the simplicity of their implementation as compared to other models.…”
Section: Introductionmentioning
confidence: 99%
“…While homogeneous models, which are useful for low void fraction and very small bubble oscillations conditions, ignore bubble dynamics and do not require Rayleigh-Plesset equation solutions, the other two approaches do require such modeling. Eulerian-Lagrangian approaches are more appropriate for higher void fractions (Spelt & Biesheuvel, 1997, Balachandar & Eaton, 2010, Raju et al, 2011, Shams et al, 2011. In a recent work by Raju et al (2011) comparing a continuum homogeneous model (Gilmore, 1952) , an Eulerian multicomponents model (Wardlaw & Luton, 2000, Wardlaw & Luton, 2003, and an Eulerian-Lagrangian model , Chahine, 2009, Hsiao et al, 2013b it was found that high-frequency local fluctuations were only captured when an Eulerian viscous solver was coupled with a Lagrangian discrete bubble dynamics and when the microscale behavior of the field bubbles was well resolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, in addition to considering the two-way coupling, the interaction between bubbles like the collision, coalescence and breakup effects are considered as well. Examples of works following this approach are Delonij et al (1996Delonij et al ( ), R ger et al (2000, Sommerfeld et al (2003), Darmana et al (2006), Shams et al (2010), Farzpourmachiani et al (2011), Movahedirad et al (2012.…”
Section: Four-way Couplingmentioning
confidence: 99%